1990
DOI: 10.1007/bf00022886
|View full text |Cite
|
Sign up to set email alerts
|

Induced parthenogenesis in kiwifruit (Actinidia deliciosa) through the use of lethally irradiated pollen

Abstract: Parthenogenetic development of seeds after pollination with irradiated pollen was studied in the dioecious species Actinidia deliciosa (kiwifruit). In total, 479 pollinations were made involving three recipient female cultivars, with five male and two hermaphrodite pollen donors. Pollen was irradiated with doses of 0.5, 0.7 and 0.9 kGy, all three doses produced parthenogenetic seeds. The 0.7 kGy dose yielded the highest number of germinating seeds (708 of a total of 723), of which 609 developed into seedlings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…Banding patterns obtained from SSR analysis of these haploid plantlets indicated their maternal origin, which confirmed that pollination with gamma-irradiated pollen at 300-400 Gy in citrus promotes the formation of parthenogenetic haploid embryos similar to that of the maternal genotype through the interruption of the normal double fertilization process. These observations are in agreement with the earlier findings reported by Raquin (1985) in Petunia, Sauton and Dumas de Vaulx (1987) in melon, Pandey et al (1990) in kiwifruit, Lespinasse (1991) andDe Witte andKeulemans (1994) in apple, Froelicher et al (2007) in mandarin, and Yahata et al (2010) in pummelo.…”
Section: Hybridity Analysis Using Ssr Markerssupporting
confidence: 94%
“…Banding patterns obtained from SSR analysis of these haploid plantlets indicated their maternal origin, which confirmed that pollination with gamma-irradiated pollen at 300-400 Gy in citrus promotes the formation of parthenogenetic haploid embryos similar to that of the maternal genotype through the interruption of the normal double fertilization process. These observations are in agreement with the earlier findings reported by Raquin (1985) in Petunia, Sauton and Dumas de Vaulx (1987) in melon, Pandey et al (1990) in kiwifruit, Lespinasse (1991) andDe Witte andKeulemans (1994) in apple, Froelicher et al (2007) in mandarin, and Yahata et al (2010) in pummelo.…”
Section: Hybridity Analysis Using Ssr Markerssupporting
confidence: 94%
“…Poir (Kurtar et al 2009), Cucumis melo (Nasertorabi et al 2012) and Actinidia deliciosa Przywara 1998, 1999;Pandey et al 1990). 2.…”
Section: Introductionmentioning
confidence: 99%
“…Since in sunflower, similar to other plant species (9,13,5), in vitro gynogenesis and androgenesis still have limited success, the technique of pollination with irradiated pollen in combination with embryo culture is an alternative approach for production of doubled haploid plants.…”
Section: Resultsmentioning
confidence: 99%
“…The method of gamma-induced parthogenesis was first successfully applied to petunia (11), and later this approach was developed and used in cabbage (3), kiwi (9,2), apple (13), onion (4), rose (6,7), tobacco (8) and other crops.…”
Section: Introductionmentioning
confidence: 99%